The effects of economic sanctions on foreign direct investment and multinational companies operating in Sudan - Abusin, Mutasim Mohammed Alhadi (2021)
Little is known about the effects of economic sanctions when it comes to Foreign Direct Investment (FDI) and Multinational Companies (MNCs) that are affected by such sanctions. The mechanisms used by foreign investors and MNCs to survive in such economic environment, and how to overcome sanctions restrictions in the host countries are yet to be explored by researchers. Therefore, the purpose of this study is to analyse the effects of economic sanctions on FDI and MNCs that operate in Sudan. It also investigated the business decisions made by these MNCs’ management to overcome restrictions imposed by the sanctions. Multiple qualitative methods were employed in this study. The first method was in the form of online questionnaires, and the second method was in the form of case studies to elicit relevant information about the impacts of the economic sanctions on the MNCs that operate in Sudan. The results from the case studies show that the MNCs from the sanction imposing countries evaluated the cost of the sanctions with the expected benefits from the operations in Sudan, and they decided to divest their activities once the sanctions cost become higher than the benefits. On the other hand, the online questionnaire’s findings reveal that MNCs decided to diversify their businesses in the primary sectors in order to lessen the effects of the economic sanctions’ restrictions. Additionally, a great number of the MNCs indicated that they were going to divest their operations in Sudan due to the heavy cost of the sanctions on their operations. Therefore, this study highlighted the need for urgent policy interventions to encourage MNCs operating in Sudan to diversify their business to the manufacturing and industrial sectors instead of divestment and leaving the county. Future studies could examine the impact of FDI and MNCs divestment on the economy of the target country.